2015 IEEE International Conference on Electro/Information Technology (EIT) 2015
DOI: 10.1109/eit.2015.7293319
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis on radiation degraded BLDC motor in robot servo systems

Abstract: For humanoid robot applications in nuclear radiation environments, not only the electronic and mechanical parts, but also the servo system in robots could be damaged by large dose of radiation. In this paper we study the radiation induced degradation to the brushless DC (BLDC) motor in the robot servo systems and analyze how its performance changes due to radiation induced demagnetization. The radiation demagnetization factor is introduced into the electromagnetic model of the BLDC motor, and the motor perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…where݇ is the power coefficient determined by the power of radiation source, ݀ ሚ (ߠ) is an random B-field intensity reduction ratio following the distribution ܰ ෩ (ߤ, ߪ ଶ ) , in which ߤ is the average reduction ratio, ߪ ଶ the variance of the same parameter.Our research in [16] has shown that the value of ݀ߖ ݀ߠ ⁄ always vary by a greater extent than the magnetic flux density ‫.ܤ‬ Therefore, the motor back-emf constant ‫ܭ‬ , will nolonger be a constant, but a number varying with the motor angular position.…”
Section: Radiation Demagnetization Modelingmentioning
confidence: 91%
“…where݇ is the power coefficient determined by the power of radiation source, ݀ ሚ (ߠ) is an random B-field intensity reduction ratio following the distribution ܰ ෩ (ߤ, ߪ ଶ ) , in which ߤ is the average reduction ratio, ߪ ଶ the variance of the same parameter.Our research in [16] has shown that the value of ݀ߖ ݀ߠ ⁄ always vary by a greater extent than the magnetic flux density ‫.ܤ‬ Therefore, the motor back-emf constant ‫ܭ‬ , will nolonger be a constant, but a number varying with the motor angular position.…”
Section: Radiation Demagnetization Modelingmentioning
confidence: 91%